A Most Unlikely Case: Chile, Pinochet and the Advance of Human Rights - Landman, Todd (Política. Revista de Ciencia Política, 2013)
This article argues that Chile has had a disproportionate effect on the international politics and law of human rights. Understood in traditional realist terms, Chile is a relatively small country that only recently joined the OECD and that should not have a great deal of impact on international affairs. Yet, for the 40 years since the 1973 military coup that overthrew the government of Salvador Allende it has received a tremendous amount of attention from other states (particularly the United States), inter-governmental organisations and international non-governmental organisations, while at the same time has had a great deal of impact on the public discourse and understanding around human rights in ways that have advanced international law and policy making. The article examines the unlikely nature of Chile’s influence on human rights at the international level while recognising that very little true justice has been achieved at the domestic level for the gross violations of human rights that had been committed during the Pinochet dictatorship. The case of Chile is thus an illustrative example of ‘the power of human rights’ that has contributed to the ‘justice cascade’ in significant way, even though true justice at home has been slow in coming.